Afflictions Related to "Ideals" of Masculinity: Gremlins Within. Issue 2 (3rd April 2017) - Brady, Mary
Abstract: The author considers the "ideals" of masculinity for boys and men and the potential for these ideals (in their extremity) to contribute to rigid psychic states and splitting. Split-off parts can return through "gremlin-like" symptoms. These symptoms are subjectively experienced as trouble making, particularly in relation to being "big" or "macho, " physically or intellectually. Women who identify with such ideals are also vulnerable to these gremlin-like symptoms. A literary example is offered as well as personal reflections of two analysts, Donald Moss and the author.